PERFORMANCE MODELING OF PRECONCEPTION POSYANDU IN BANGGAI REGENCY - Sutadi Lanyumba, Fitrianty; Syafar, Muhammad; Darmawansyah, Darmawansyah; Indarty Moedjiono, Apik; S. Otoluwa, Anang; Jihadi, M (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Measuring the performance of the Preconception Posyandu is an obligation in maintaining the existence of these services because it is part of the role in solving the current problems of AKI, AKB and stunting Objective : The purpose of this study is to model the performance of Preconception Posyandu in Banggai Regency using indicators from the Europan Foundation Quality Management (EFQM) performance assessment framework Research Methods/ Implementation Methods : This type of research is analytics using SEM analysis for modeling. The sample in this study is Village Midwives and Preconception Women with a total of 255 each who were selected using the purposive sampling technique Results : The results of the study show that in the outer model, 4 indicators are known to be invalid and reliable because the AVE value < 0.50 and the CA value < 0.70. The indicators in question are indicators of information systems (TSI), indicators of SOPs (TSOP), indicators of increasing TT immunization coverage (CITT) and indicators of decreasing the prevalence of nutritional anemia (AG). Meanwhile, in the inner model, it is known that there are 2 paths that are insignificant because the t-value statistically < 1.96 and the p value > 0.05, namely the variable path of customer satisfaction to the variable of performance results and the variable of impact on society on the variable of performance results Conclusion/Lesson Learned : From the results of the study, it can be concluded that although the variables of customer satisfaction and the impact on the community do not have a direct effect on the performance results of the preconception Posyandu, these two variables will still be supportive factors in achieving the overall performance of the Preconception Posyandu.